Development of Melampsora Leaf Rust in Nursery Grown Populas ciliata - Sharma, R. C.; Khan, Y.; Gupta, A. K. (Indian Forester, 2002)
Development of Melampsora leaf rust in Populus ciliata reveals that clones, which were disease free during July, got infected in the month of August. Clone Kufri has least disease while Theog was most susceptible. Disease development was rapid between July and August months. PCM 5195, 5011, 5180 and 5157 hybrids of P. ciliata x P. maximowiczii had least disease while PCM 5084 and 5053 were highly susceptible. The development of disease was negativelycorrelated with temperature but positively with relative humidity and rainfall.